Aplicação da Teoria Geral dos Sistemas no Credenciamento de Organismos de Inspeção na Área de Segurança Veicular - Nóbrega, Ricardo Barcelos da (2003)
The sharp growth in the number of inspection bodies applying for accreditation in the area of automobile safety requires the creation and implementation of a new approach toward work and social interaction by the authorities responsible for the accreditation process. The main responsibility for the recognition of technical competence of inspection bodies accreditation belongs to Inmetro. This agency has legal attributions to act as an accreditation body and it is internationally recognized as the Brazilian accreditation body for organizations and laboratories. This paper is a survey into the institutional mechanism that acts in the accreditation system, trying to understand its domain and offer ways and means for its continuous improvement. Taking into consideration practical experiences, it was observed that the tasks concerned are multidisciplinary and only after restructuring the procedures and putting them into practice, under absolute control, would the second phase be viable, which was taking the system as a whole into consideration. During the first phase, the work was based on the theories of International Standardization Organization (ISO) concerning to quality management, while the second phase was based on the General Systems Theory. This theory showed how to overcome the problem of joining the dispersed knowledge carried by specialists and also found new resolutions on how to solve problems that came up such as local problem solutions. Time distribution among the staff has been improved, and, in a broad view, the General Systems Theory provided improvement in the accreditation credibility and inspection services as well as in accreditation independence and impartiality